Deep liquid tanks in seismic response control of asymmetric high-rise buildings. (November 2022) - Das, Anupam; Maity, Damodar; Bhattacharyya, Sriman Kumar
Abstract: The present work investigates the usefulness of installing deep liquid storage tanks (DLTs) on the roof of high-rise buildings with plan irregularity. The aim is to assess the damping efficiencies of DLTs in reducing responses of high-rise buildings with plan irregularity, considering the effect of their placement and direction of the external excitation. A DLT has a higher liquid depth to tank length ratio as compared to the traditional tuned liquid dampers (TLDs). A 70 m tall, 20-storey reinforced concrete framed building with asymmetry in plan is considered for the numerical assessment. The system coupling facility of ANSYS Workbench is utilized to study the structure-fluid coupled dynamics. ANSYS Transient Structural module solves the structure part using the finite element analysis (FEA), whereas, ANSYS (FLUENT) uses the finite volume method (FVM) to solve the fluid part. The authors [1] developed a practical framework to demonstrate the efficacy of DLTs for symmetrical building, which is extended in the present study for asymmetric building. In this paper, the validity of the framework is presented through an equivalent tuned mass damper (TMD) analogy. It is observed that for an asymmetric high-rise building, eccentric placement of DLT gives better response reduction, both in terms of peak roof displacement and acceleration.